Changes in oxygenation and pulmonary haemodynamics in preterm infants treated with inhaled nitric oxide. Issue 3 (1st November 1997) - Subhedar, N V; Shaw, N J
Abstract : AIM: To investigate changes in various cardiorespiratory variables with inhaled nitric oxide (NO), as part of a randomised controlled trial. METHODS: Infants were treated with inhaled NO for 72 hours. Changes in oxygenation were assessed using the oxygenation index (OI). Serial changes in pulmonary artery pressure (PAP) were assessed using the Doppler derived acceleration time to right ventricular ejection time ratio (AT:RVET). Doppler measurements of right ventricular output, pulmonary blood flow, and systolic PAP was performed in a subset of infants. RESULTS: Twenty infants received inhaled NO and 22 acted as controls. Infants were treated at a median dose of 5 (range 5 to 20) ppm. There was a fall in median OI by 17% in treated infants within 30 minutes of treatment. The fall in OI in treated infants was significantly different from the response in controls until 96 hours. Infants treated with inhaled NO showed a rapid response with a median rise in AT:RVET of 0.04 (range −0.06 to 0.12) within 30 minutes. The change in AT:RVET was significantly different from controls until 4 hours. Median systolic PAP also fell in treated infants by 6.1 (range −14.4 to −4.4) mm Hg within 1 hour. Changes in OI were significantly associated with changes in PBF (r = 0.44), but not with changes in AT:RVET. CONCLUSION: Treatment with inhaled NO rapidly improves oxygenation and lowers PAP in preterm infants. However, these effects are transient and treatment does not influence long term outcome.